Improvement of Power Quality in a Three-Phase System Using an Adaline-Based Multilevel Inverter - Das, Soumya Ranjan; Ray, Prakash K.; Sahoo, Arun Kumar; Balasubramanian, Karthik; Reddy, Gaddam Sanjeeva (Frontiers in energy research, 2020)
The existence of harmonics in the power distribution system (PDS) is treated as the most serious issue that affects its stability and reliability. The active power filter (APF) therefore plays a vital role in PDS to compensate for the harmonics for the improvement of the power quality (PQ) and to keep the total harmonic distortion (THD) below 5% as per IEEE-519. In this work, a three-phase four-wire (3P-4W) multi-level inverter (MLI)-based APF is proposed to overcome the shoot-through effect (STE) and reduce the distortions in the supply current. The control of the voltage source inverter (VSI) is achieved using an Adaline-based LMS (A-LMS) algorithm with a hysteresis current controller. The proposed filter that uses the A-LMS technique is compared with the conventional recursive least square (RLS) algorithm. The A-LMS approach is mainly operated for maintaining the dc link voltage of MLI, which follows the principle of capacitor energy and reduces the total harmonic distortion (THD) under different load variations. The performance of MLI under different load conditions is designed, developed, and validated by using a MATLAB/Simulink environment, and the preeminent features are established.